2001
DOI: 10.1046/j.1471-4159.2001.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

A single β subunit M2 domain residue controls the picrotoxin sensitivity of αβ heteromeric glycine receptor chloride channels

Abstract: This study investigated the residues responsible for the reduced picrotoxin sensitivity of the ab heteromeric glycine receptor relative to the a homomeric receptor. By analogy with structurally related receptors, the b subunit M2 domain residues P278 and F282 were considered the most likely candidates for mediating this effect. These residues align with G254 and T258 of the a subunit. The T258A, T258C and T258F mutations dramatically reduced the picrotoxin sensitivity of the a homomeric receptor. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 37 publications
13
121
2
Order By: Relevance
“…Furthermore, other reports have demonstrated little or no usefacilitated block by picrotoxin in glycine and GABA C receptors, respectively (13,21). Thus, picrotoxin might bind at an allosteric site to stabilize a closed or desensitized state of these channels (11,12,27). To resolve the complexity of the picrotoxin interaction with these channels, the existence of multiple binding sites for picrotoxin has been suggested (7,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other reports have demonstrated little or no usefacilitated block by picrotoxin in glycine and GABA C receptors, respectively (13,21). Thus, picrotoxin might bind at an allosteric site to stabilize a closed or desensitized state of these channels (11,12,27). To resolve the complexity of the picrotoxin interaction with these channels, the existence of multiple binding sites for picrotoxin has been suggested (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated residues in the cytoplasmic aspect of TMII as the picrotoxin binding site (27, 29 -31). Mutations introduced at both the 2Ј and 6Ј positions of TMII confer PTX resistance (15,16,27). Picrotoxin can protect a cysteine engineered into the 2Ј position from irreversible modification by reactive sulfhydryl reagents (29).…”
Section: Discussionmentioning
confidence: 99%
“…Both picrotoxin and the native ginkgolides have been shown to form interactions with the 6Ј residues in the M2 helices lining the ion channel pore (18 -20, 25, 27, 28). Furthermore, the 2Ј M2 residue, located one helix turn below, has been proposed to be involved in the binding of picrotoxin (25,28) and to be involved in the coordination of the ginkgolides to the heteromeric ␣1␤ GlyR but not to the homomeric GlyR (19,20). In structure-activity relationship studies of ginkgolide analogs, the GlyR antagonist activity of the ginkgolide has been demonstrated to be very dependent on its rigid structure, and modifications of the hydroxyl groups in the molecule have been found to have detrimental effects on its activity (24,29).…”
Section: ␣1mentioning
confidence: 99%
“…The 6Ј residue in the bottom half of the M2 ␣-helices forming the ion channel of the GlyR have been shown to be involved in binding of native ginkgolides as well as picrotoxin and its two components picrotin and picrotoxinin (19,20,25,27,28). The 6Ј residue is highly conserved through the Cys-loop receptor family, being a Thr or a Ser residue in almost all subunits (Fig.…”
Section: The Molecular Basis For Subtype Selectivity Of Ginkgolide X mentioning
confidence: 99%
See 1 more Smart Citation